Effectiveness of Kisan Mobile Advisory Service in Dissemination of Agricultural Information in Gandhinagar District of Gujarat (Indian Journal of Extension Education, 2019)
The revolution in ICT has made access to the information easy and cost effective to the rural masses in general and farming community in particular. Kisan Mobile Advisory (KMA) service is one among the several methods of ICTs working successfully for dissemination of latest information. KMA service was launched for sending information through mobile Short Message Service (SMS) in Gandhinagar District of the Gujarat State through Krishi Vigyan Kendra (KVK) during May 2014. The content of messages were typed in Gujarati language and information related to crop production, crop protection, vegetable and fruit production, dairy farming, weather forecasting, post harvest management, government Schemes and other enterprises sent to end users. Out of total registered 18750 users with us, 90 farmers, 25 Extension personnel and 15 input dealers were randomly selected for this study. After sending messages for two years (2017, 2018) feedback was sought during April May 2019. Total 78 messages on different discipline were sent during study period. For collecting information, semi structured interview schedule was designed. The delivered messages were highly understandable for 80 per cent of extension personnel, 60 per cent of input dealers and 42.22 per cent of farmers. Messages were needful and timely as reported by 80 percent of farmers, 72 per cent of extension personnel and 66.66 per cent of Input dealers. The messages were fully applicable perceived by 51.11 per cent of farmers. It was found that 68 per cent messages were fully applicable for extension personnel and 46.66 per cent for input dealers. It was found that technology imposes high impact on 62.22 per cent of KMA members of farmer category, whereas 72 per cent and 60 per cent members of extension personnel and input dealers category reported technology impacted highly on them. Low impact was reported by 12.22 per cent by farmers, 8 per cent by extension personnel and 13.33 per cent by input dealers in Gandhinagar district of Gujarat state.